Anti-stress Effects of Chrysin on Rats: A Metabolomics Study - khadijeh Haghighat; Fariba Mahmoudi; Maryam khoshkam; Homayoun Khazali (Pharmaceutical Sciences, 2025)
Background: Chrysin is a phytochemical compound and was found to be a potent anti-anxiety and neuroprotective. However, it is unclear whether chrysin has beneficial effects on stress-related metabolomic profiles. The current study aimed to assess the anti-stress effects and corresponding mechanisms of chrysin on male rats using a metabolomics method. Methods: The male rats weighing 220 ± 10 g segregated into different groups (n = 6). To induce stress, animals subjected to stress for 2 hours. The control and stressed groups received saline. Also, the intact and stressed groups, received chrysin at doses of 10 mg/kg intraperitoneally (IP). Then, behavioral tests were performed. All injections performed 30 min before stress induction. Then the serum was collected. The metabolic profiles were analyzed using the HNMR method. Results: Serum metabolic profiling showed comprehensive metabolic variation among the four groups. A series of metabolic pathways including pyrimidine, arginine and phenylalanine-tyrosine-tryptophan biosynthesis were affected. Eighteen potential biomarkers such as phenylalanine, tyrosine, alanine and arginine were identified. Chrysin could correct the disturbed metabolic pathways and restore the variation of these potential markers (P ≤ 0.05). Also, behavioral tests showed a significant improvement in anxiogenic behaviors in the male rats receiving chrysin compared to the stress group (P ≤ 0.05). Conclusion: The metabolic changes and the associated pathways, provide insights into the mechanisms of anti-anxiety of chrysin, and further studies are needed to confirm its anti-anxiety effect.